Flow‐dependent predictability of the North Atlantic jet. Issue 10 (30th May 2013) - Frame, T. H. A.; Methven, J.; Gray, S. L.; Ambaum, M. H. P.
<x xml:space="preserve">Abstract</x> [1] The North Atlantic eddy‐driven jet is a major component of the large‐scale flow in the northern hemisphere. Here we present evidence from reanalysis and ensemble forecast data for systematic flow‐dependent predictability of the jet during northern hemisphere winter (DJF). It is found that when the jet is weakened or split, it is both less persistent and less predictable. The lack of predictability manifests itself as the onset of an anomalously large instantaneous rate of spread of ensemble forecast members as the jet becomes weakened. This suggests that, as the jet weakens or splits, it enters into a state more sensitive to small differences between ensemble forecast members, rather like the sensitive region between the wings of the Lorenz attractor.